Placemaking in Practice Volume 2 : Engagement in placemaking: Methods, strategies, approaches - Aleksandra, Djukic,; Fathi, Mastoureh,; García-Esparza, Juan A.,; Hansen, Preben,; Manahasa, Edmond,; Rotondo, Francesco, (Social Sciences E-Books Online, Collection 2025., 2025)
Starting from theoretical concepts and experiences, the volume is interested in a variety of methods, techniques, approaches and conceptualisations that shape these engagements as well as different methodologies. Engage the community of residents, of different interests, of virtual communities, and community of places at different scales, understanding how these forms of engagements were achieved by using particular methods. Also, the combination of different groups engaged in the placemaking like professionals, citizens, stakeholders, NGO, students and combination of virtual and physical communities is in the very aim of the chapters. See Less